Modernism's inhuman worlds - Tazudeen, Rasheed 1983- (Cornell University Press, 2024)
"Study of animal metaphor in particular and the literary representation of animals more generally in the Victorian and modernist periods"
Keywords: Ökologie -- Motiv; Moderne; Rätsel -- Motiv; Metamoderne; Unmenschlichkeit -- Motiv; Literatur; English literature / 19th century / History and criticism; Animals in literature; Modernism (Literature) / English-speaking countries; Metaphor in literature; Modernism (Literature); English-speaking countries; 1800-1899; Criticism, interpretation, etc